COMPARING BASAVANNA WITH R.W. EMERSON’S TRANSCENDENTALISM - SURAIYA AFREEN (International Journal of Multidisciplinary Research and Studies, 2021)
Today's human issues are more difficult to solve than they have ever been. There is no doubt that mankind has amassed an incredible amount of information and power; but, these things have generated unprecedented changes, and as a result, life has become even more confusing and perplexing. Totally everything about us is in the process of changing. Given the current state of affairs, the need for spiritual ministry is more pressing now than it has ever been in the course of our nation's history. We may learn how to develop the spiritual stamina we require to get ourselves out of the rut of everyday monotonous circumstances from the great poets and saints who have lived throughout history. Basaveshwara, also known as Basavanna, was a saint from the Indian state of Karnataka. He was also a poet and an ardent social reformer. He is considered to be one of India's most influential spiritual instructors. The teaching of Basaveshwara takes on a new level of relevance when placed in the context of modern India's shifting social landscape and increasing religious consciousness. The Indian society of today is undergoing a process of self-transformation. At the core of this transformation are the concepts of democracy and nationalism, as well as an emphasis on the dissemination of education and a scientific worldview. The dominant school of thinking in the world is a significant source of inspiration for it. Our ways of thinking are shifting so drastically that it appears difficult for some of our more traditional values, institutions, and practises, such as castes, creeds, and rituals, as well as our blind beliefs, to continue existing in their current forms. Although Basavanna lived 800 years ago, he comes across to us as fully modern and practical; as a result, the lessons that he taught are still applicable in present times. If only that instruction had been followed, it would have been possible to paint a very different picture of Indian society.